A PROPOSAL FOR APPLYING THE KAIZEN METHOD IN YOUTH AND PROFESSIONAL SPORTS (Heritage, 2024)
The purpose of this study is to examine the prevalence and applicability of the Kaizen approach in sports. Because it is a widespread phenomenon with great social and cultural significance, sport is prone to highly dynamic, discontinuous, non-linear, and uncertain changes. Major changes (kawar)[1] that affect sport as a social and economically important activity in today’s unstable environment pose risks to both the management and the player. The idea behind using the Kaizen approach in sports and the sports industry is to encourage individual participation and continual improvement through a clear and detailed procedure that is tailored to the genuine requirements of every professional athlete. Globalization and socio-technological advancements have had a significant impact on sports and sports activities, and success is now solely determined by monetary value. The Kaizen method can improve the efficiency of every individual, every athlete, and even sports organizations. As a team, the management of the sports organization can accomplish the goals set before itself more quickly with the application of the appropriate Kaizen method, with the quality setting of the operational and logistics management, with gradual and continuous improvement of the makeup and organization of its operations. It is acknowledged that spreading the Kaizen method outside of its country of origin is a powerful tool that aims at the rationalization and effective utilization of all available resources. The goal of the Kaizen technique is constant improvement, which eliminates all unrealistic factors that influence how sports values, such as results, are achieved.
Keywords: Kaizen, sport, Japan, globalisation, managment